Management of bilateral conjunctival squamous carcinoma following ocular cicatricial pemphigoid: A case report and review of literature. Issue 3 (May 2023) - Franco, Elena; Salgari, Niccolò; Dugo, Marco; Franco, Maria; Stefanelli, Antonio; Franco, Filippo
The purpose of this study is to report a case of bilateral highly locally invasive conjunctival squamous neoplasia in the clinical setting of ocular cicatricial pemphigoid (OCP), and to review the available literature about this rare association. Case description: A man presented with chronic bilateral conjunctivitis and forniceal foreshortening. He had been previously diagnosed with OCP, and received proper therapy with systemic Dapsone and local steroids. After six months from treatment initiation, the patient complained of worsening symptoms and underwent two more biopsies, revealing a bilateral conjunctival squamous neoplasia.Conclusion: In rare cases, OCP can be associated with conjunctival squamous neoplasia. In case of suspected clinical modifications, it is important to make an early diagnosis by repeating several conjunctival biopsies or by performing less invasive diagnostic techniques (e.g. impression cytology of the ocular surface epithelium) to avoid unnecessary surgical damages.